(untitled) (2014)
Based on a critical discourse analysis, the theory of social mediation and political economy of communication, the theoretical foundations, methodological route and the main findings of a doctoral research work are described in this article. The objective is to analyze the conceptual and referential map with which a concept is being developed and has appeared in recent years to define a broader phenomenon, yet ambiguous, such as the digital divide; which is also part of discursive threads related to the inclusion of ICT, Information and Communication Technologies. The identification of the linguistic set of structures found in the discourses analyzed has been focused on the recognition of systems of knowledge that can be seen in the various expressions about social phenomena.